Effect of Growth Rate on Microstructure and Corrosion Resistance of Micro-arc Oxidation Coatings on Magnesium Alloy. Issue 9 (September 2017) - Hairong, Dong; Ying, Ma; Sheng, Wang; Xiaoxin, Zhao; Huixia, Guo; Yuan, Hao
Abstract: AZ91D magnesium alloys were processed by micro-arc oxidation (MAO) in silicate-containing electrolyte. The key factor of this research is a unique experimental design to fabricate coatings with the same thickness but by different power voltages which represents different growth rate. The coatings with the same thickness correspond to different coating growth rates of 1, 5, 15 and 25 μm/min, which makes the comparison and analysis-targeted microstructure and corrosion resistance of the coatings academic and practical. The coating growth rate demonstrates considerable influence on surface porosity, size and amount of micro-pores, mass and mass to thickness ratio, and anti-corrosion property of the coatings based on both qualitative and quantitative analysis, but it is not the case for the composition and element distribution of the coatings. An industrial application-oriented selection of appropriate coating growth rate, which demands for both productive efficiency and good performance, has to be considered together with anti-corrosion property of the coatings. The case of the coating fabricated with the growth rate of 15 μm/min supports this point strongly.